2009
DOI: 10.1645/ge-1988.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Gnathostoma turgidum an Annual Parasite of Opossums? Drastic Seasonal Changes of Infection in Didelphis virginiana in Mexico

Abstract: Gnathostoma turgidum is a nematode that parasitizes the stomach of opossums, Didelphis virginiana. Despite its wide distribution in the Americas, its natural life cycle is poorly understood. Recently, we found an endemic area for G. turgidum infection in Sinaloa, Mexico (Diaz-Camacho et al., 2009). Based on sporadic surveys for several years, the prevalence was apparently high in summer and extremely low in winter. To confirm that this is really a seasonal variance, we conducted a longitudinal survey on G. tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…OAXACA: Temascal: Philander opossum ( Almeyda-Artigas et al 2010 ), Didelphis marsupialis ( Almeyda-Artigas et al 2000 , Oceguera-Figueroa 2002 , Mosqueda-Cabrera 2003 ), Didelphis virginiana ( Lamothe-Argumedo et al 1998 , Almeyda-Artigas et al 2000 , Mosqueda-Cabrera 2003 ). SINALOA: Tecualilla: Didelphis virginiana ( Nawa et al 2009 , Díaz-Camacho et al 2009 ). TABASCO: Rancho Mendoza Llergo: Didelphis marsupialis ( León-Règagnon et al 2005 ); Jardín Botánico de la UJAT, Oriente Segunda Sección, Ranchería El Limón, Ranchería Emiliano Zapata, Ranchería José María Pino Suárez, Ranchería La Palma: Didelphis marsupialis ( Gallegos-Torres 2003 ).…”
Section: Resultsunclassified
“…OAXACA: Temascal: Philander opossum ( Almeyda-Artigas et al 2010 ), Didelphis marsupialis ( Almeyda-Artigas et al 2000 , Oceguera-Figueroa 2002 , Mosqueda-Cabrera 2003 ), Didelphis virginiana ( Lamothe-Argumedo et al 1998 , Almeyda-Artigas et al 2000 , Mosqueda-Cabrera 2003 ). SINALOA: Tecualilla: Didelphis virginiana ( Nawa et al 2009 , Díaz-Camacho et al 2009 ). TABASCO: Rancho Mendoza Llergo: Didelphis marsupialis ( León-Règagnon et al 2005 ); Jardín Botánico de la UJAT, Oriente Segunda Sección, Ranchería El Limón, Ranchería Emiliano Zapata, Ranchería José María Pino Suárez, Ranchería La Palma: Didelphis marsupialis ( Gallegos-Torres 2003 ).…”
Section: Resultsunclassified
“…Moreover, they showed high identity with that of a patient from Nayarit, Mexico (10), with only a single nucleotide polymorphism. In addition, our previous study demonstrated that G. binucleatum is the etiological agent for human gnathostomiasis in an endemic area of Sinaloa, Mexico, despite the fact that the G. turgidum life cycle takes place in the same geographical area (12)(13)(14)23,27,28). Thus, G. binucleatum is the only species associated with the disease in the Americas (7).…”
Section: Discussionmentioning
confidence: 98%
“…1). In Sinaloa, the AL3A of G. binucleatum has been identified in different species of fish, birds, and reptiles, whereas adult worms and AL3A of G. turgidum have only been isolated from opossums (Didelphis virginiana) (12,13).…”
Section: G N a T H O S T O M I A S I S I S A F O O D -B O R N E Z O Omentioning
confidence: 99%
“…Both Gnathostoma species have been reported in the endemic area, suggesting that they co-inhabit the same location. The prevalence of G. turgidum, an annual parasite of Didelphis virginiana, is highest during May and June (Nawa et al ., 2009). It has been reported that advanced third-stage larvae (A3L) localize to the liver of infected animals from February to April, and subsequently adult worms are located in the stomach from April to July (Díaz-Camacho et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%